Profiles of heart failure in adolescents and young adults with congenital heart disease. (December 2018) - Guccione, Paolo; Iorio, Fiore S.; Rebonato, Micol; Bennati, Elena; Spaziani, Gaia; Amodeo, Antonio; Perri, Gianluca; Parisi, Francesco; Favilli, Silvia
Abstract: Heart failure is an important cause of late morbidity and mortality in children, adolescents, and young adults with congenital heart disease. Heart failure is the first cause of mortality in adult congenital heart disease population accounting for 30% to 50% of death while the incidence related to ventricular arrhythmias accounts for another 20%. Symptomatic heart failure requiring hospitalization is associated with 3% to 5% mortality during hospital stay and a 25% incidence of death within the first year after admission. Patients at highest risk for death as a result of heart failure are those with single-ventricle physiology or systemic right ventricular anatomy; however, patients with left-sided obstruction or chronic volume overloaded right ventricle are also at a higher risk than the general population. Medical therapy is scarcely effective in most cases of congenital heart disease related heart failure in children, adolescents and young adults. Lack of donors limits access to heart transplantation and results in adult congenital heart disease population are worse than those in other cardiac populations with heart failure. Highlights: Most children with congenital heart disease (CHD) are expected to reach adulthood. The probability of developing heart failure increases with age and severity of CHD. Conventional concept of heart failure cannot be applied to the population with CHD. An effective transition from pediatric to adult-oriented care is strongly warranted. Evidence of pharmacological therapy in heart failure in CHD is limited.